Detection of polydimethylsiloxanes transferred from silicone-coated parchment paper to baked goods using direct analysis in real time mass spectrometry - Jakob, Andreas; Crawford, Elizabeth A.; Gross, Jürgen H. (Journal of mass spectrometry, 2016)
The non-stick properties of parchment papers are achieved by polydimethylsiloxane (PDMS) coatings. During baking, PDMS can thus be extracted from the silicone-coated parchment into the baked goods. Positive-ion direct analysis in real time (DART) mass spectrometry (MS) is highly efficient for the analysis of PDMS. A DART-SVP source was coupled to a quadrupole-time-of-flight mass spectrometer to detect PDMS on the contact surface of baked goods after use of silicone-coated parchment papers. DART spectra from the bottom surface of baked cookies and pizzas exhibited signals because of PDMS ions of the general formula [(C2H6SiO)n + NH4]+ in the m/z 800-1900 range. Copyright © 2016 John Wiley & Sons, Ltd.
Gesehen am 30.04.2020